Dez mandamentos de Jorge Furtado: cartografias em três platôs - Guidotti, Flávia Garcia (Universidade do Vale do Rio do Sinos, 2007)
Jorge Furtado's tem commandments: cartographies on tree plateaus map a group of thirteen movies. Tem short movies and tree full-length ones. All of them written and direct by Jorge Furtado. For that purpose, concepts from contemporary philosophy were used. Specially the ones developed by Gilles Deleuze. The study is organized in three plateaus. In the first one are the narratives built through my contact with the movies, that is, through the narrator-researcher-viewer's experience with the object of her study. In the second plateaus are the conceptual plots which worked as a basis or plane of immanence, where the dissertation study lay on. In this one multiplicity and mapping concepts were studies, as well as some terms related to issues concerning authorship. These concepts allow us to reflect on the movies and is called here "Jorge Furtado's ten commandments". In these commandments the following reflections are found: 1) the relationship between reality and fiction aroused by Jorge Furtado's movies; 2) the
Keywords: cineasta; crítica; diretor; filme; interpretação; cinema; Furtado, Jorge; Ciências Sociais Aplicadas